Jacques Derrida's "Des humanités et de la discipline philosophique"/"Of the Humanities and Philosophical Disciplines": Roundtable Discussion - Adams, Hazard; Behler, Ernst; Birus, Hendrik; Derrida, Jacques; Iser, Wolfgang; Krieger, Murray; Miller, Hillis; Pfeiffer, Ludwig; Readings, Bill; Wang, Ching-hsien; Yu, Pauline (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
This roundtable discussion of "Des humanités et de la discipline philosophique" ("Of the Humanities and Philosophical Disciplines"), Jacques Derrida's contribution to the first International Conference for Humanistic Discourses, was held in April, 1994. The papers of this first meeting of the ICHD have been published in volume 4 of Surfaces (1994).